Video Interaktif Sebagai Media Interpretasi Gerak Tari Tradisional Siswa SMP - Raka Sukma Dewi; I Wayan Karja; I Gusti Putu Sudarta; Gede Pasek Putra Adnyana Yasa (Jayapangus Press, 2026)
This study aims to analyze the effectiveness of interactive videos in overcoming visibility constraints and students' psychological anxiety in traditional dance learning. Employing a descriptive-analytical qualitative approach, data were collected through observation, interviews, and Likert scale questionnaires from 30 8th-grade students and 1 teacher at SMP Nasional Denpasar. The results show that the slow motion and multi-angle features significantly reduce visual distortion, thereby increasing the accuracy of students' complex movement interpretations. Psychopedagogically, the use of personal devices successfully created a